Conservatism as an Ideology in Inglorious Basterds (2009) - Jumino, Jumino (Fakultas Ilmu Budaya Universitas Diponegoro, 2021)
Conservatism is one of the ideological expressions to maintain the circumstances and power in society. One of the popular literary works that depict conservatism as an ideology is Tarantino’s movie “Inglorious Basterds.” The idea of conservatism as an ideology is represented through the central characters in the plot, the “Basterds.” This study aimed to analyze the representation of conservatism as an ideology in the movie Inglorious Basterds. The writers applied a sociological approach and analyzes the social behavior and social history depicted by the characters in the movie. According to the findings, conservatism’s representation as an ideology is shown by the characterization of the “Basterds” that uphold their rules, value, and tradition. However, it does not mean they cannot accept other values or traditions completely. The writers also found that the movie challenges the standard American remembrance of World War II. Consequently, it is essential to highlight that conservatives do not dishonor and reject other norms, values, or traditions.Keywords: Ideology; Conservatism; Popular literature